2017
DOI: 10.1007/s11999-016-4755-x
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Bone Grafting in Giant Cell Tumor of the Extremity Reduces Nononcologic Complications

Abstract: Background Giant cell tumors (GCTs) are treated with resection curettage and adjuvants followed by stabilization. Complications include recurrence, fracture, and joint degeneration. Studies have shown treatment with polymethylmethacrylate (PMMA) may increase the risk of joint degeneration and fracture. Other studies have suggested that subchondral bone grafting may reduce these risks. Questions/purposes Following standard intralesional resection-curettage and adjuvant treatment, is the use of bone graft, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 30 publications
0
65
0
Order By: Relevance
“…Given this, some have suggested that an allograft buffer prevents thermal necrosis of the chondrocytes by the bone cement exothermic reaction. 20, 21 Benevenia et al evaluated the effectiveness of the addition of allograft between the bone cement and articular cartilage and found that this technique lowered the incidence of osteoarthritis, but did not increase the incidence of local recurrence. This use of both bone graft and bone cement around knee has been demonstrated in preventing mechanical failure.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Given this, some have suggested that an allograft buffer prevents thermal necrosis of the chondrocytes by the bone cement exothermic reaction. 20, 21 Benevenia et al evaluated the effectiveness of the addition of allograft between the bone cement and articular cartilage and found that this technique lowered the incidence of osteoarthritis, but did not increase the incidence of local recurrence. This use of both bone graft and bone cement around knee has been demonstrated in preventing mechanical failure.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…To date, several studies indicated that less residual subchondral bone and larger area of the subchondral bone invaded by GCT were more likely to accelerate the procedure of degenerative changes in the bone [ 4 , 5 ]. Supplemental bone grafting in the subchondral bone area might reduce the degenerative development [ 6 , 7 ]. Considering that destruction of the articular cartilage and subchondral bone due to extensive curettage led to occurrence of mechanical failure; it was crucial to figure out reliable clinical measurements to predict and reduce this risk.…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors believed that a radiolucent zone might allow micromotion between the bone and cement which might cause fractures. [ 32 33 ] For this present series, no patient in cementation group got postoperative bone fracture while one patient in bone grafting group had postoperative bone fracture. The options of fixation should be decided by the tumor location, tumor volume, Campanacci's grade, and other factors.…”
Section: Discussionmentioning
confidence: 64%